Role of toll-like receptors and nod-like receptors in acute lung infection - Le, John; Kulatheepan, Yathushigan; Jeyaseelan, Samithamby (Frontiers in Immunology, 2023)
The respiratory system exposed to microorganisms continuously, and the pathogenicity of these microbes not only contingent on their virulence factors, but also the host's immunity. A multifaceted innate immune mechanism exists in the respiratory tract to cope with microbial infections and to decrease tissue damage. The key cell types of the innate immune response are macrophages, neutrophils, dendritic cells, epithelial cells, and endothelial cells. Both the myeloid and structural cells of the respiratory system sense invading microorganisms through binding or activation of pathogen-associated molecular patterns (PAMPs) to pattern recognition receptors (PRRs), including Toll-like receptors (TLRs) and NOD-like receptors (NLRs). The recognition of microbes and subsequent activation of PRRs triggers a signaling cascade that leads to the activation of transcription factors, induction of cytokines/chemokines, upregulation of cell adhesion molecules, recruitment of immune cells, and subsequent microbe clearance.Since numerous microbes resist antimicrobial agents and escape innate immune defenses, in the future, a comprehensive strategy consisting of newer vaccines and novel antimicrobials will be required to control microbial infections. This review summarizes key findings in the area of innate immune defense in response to acute microbial infections in the lung. Understanding the innate immune mechanisms is critical to design host-targeted immunotherapies to mitigate excessive inflammation while controlling microbial burden in tissues following lung infection.